Bactericidal and anti-inflammatory activity of defined hypochlorite solution - Christopher David Chapman; Myles Hyla Edward Dakin; Richard Aspinall (PLoS ONE, 2026)
Background Hypochlorite is an antiseptic that has been used for over a century for industrial sterilisation and antisepsis. More recently, the topical application of hypochlorite to severe burn patients increased their rate of survival post infection with Gram-negative bacteria, of which antisepsis cannot be solely responsible. Methodology Broth microdilution experiments were performed to confirm anti-microbial activity. Cytokine exposure was performed by dialytic exposure of serum spiked with either interleukin-6 or interleukin-10, accounting for contextually appropriate organic load. Cytokine degradation was measured by immunoassay and by functional bioassay utilising HEK-Blue cells. Hypochlorite mediated cytotoxicity against dermal cells was assessed via direct exposure, followed by a 1-hour attenuation period. Resazurin was utilised to assay the impact of hypochlorite on cell viability. Results We have shown that this formulation of hypochlorite in isotonic saline has multiple mechanisms. The first is that 7 mmol/L hypochlorite is capable of eliminating both Gram-negative and Gram-positive bacteria, and that the same concentration differentially degrades the function of IL-6 and IL-10. IL-6 was seen to be 3 times more susceptible to loss of function than IL-10 after only 5 minutes of exposure ( P < 0.005). The asymmetrical effect on these cytokines was observed between 7 and 1.75 mmol/L, and across the entire time scale examined. This hypochlorite formulation has the capability to sterilize a wound, and by altering the cytokine profile reduce inflammation and scarring, and improve wound healing. Conclusions These findings, taken with the burn survival study, suggest that the increased survival rate after application of hypochlorite could be due to the combined effect of elimination of infective pathogens, and the differential degradation of interleukin-6 and interleukin-10 at the site of injury.